Photocatalytic activation of inert bonds and their functionalization via hydrogen-evolution cross-couplings - Tung, Chen-Ho (2020)
Cross-Coupling reactions are potential tools for construction of complex molecular frameworks of diversified interests via formation of carbon-carbon (C-C) or carbon-heteroatom (C-X) linkage. Compared with conventional transition metal-catalyzed cross-couplings and oxidative crosscouplings, photocatalytic hydrogen-evolution cross-couplings allow used of less functionalized reagents and proceed without any sacrificial oxidant under mild conditions and by visible-light irradiation. The reactions generally afford the desired cross-coupling products with excellent yields, and hydrogen gas is the only byproduct. In this presentation we will highlight the progress of these reactions in our group.